PENGEMBANGAN SISTEM ADMINISTRASI KEPENDUDUKAN SECARA DARING PADA KELURAHAN MANGGARAI JAKARTA - erni rihyanti (IULI Publisher, 2022)
The development of information technology has developed very quickly following the times that require speed and accuracy in all aspects of life. The internet has made it easy to communicate and get information quickly and accurately. Manggarai Village, which is located in the Tebet District, Jakarta Capital Special Region, is one of the areas where the bureaucracy has not utilized today's technology, so that it makes researchers want to design a website-based administrative application to facilitate the community in bureaucratic activities in Manggarai Village. Keywords : Population Administration, Reports, Society, Online, Website.